Blade Runner : My Story - Pistorius, Oscar (London Virgin Books, 2012)
Blade Runner is the inspirational memoir of Oscar Pistorius. It is the one who sits and watches, and has never tried to run.' On discovering that their son had been born with no fibulae, Oscar's parents made the difficult decision to have both his legs amputated, giving him the best possible chance of a normal life.
Keywords: Runners (Sports) -- Pistorius, Oscar, 1986- -- South Africa -- Biography